ANALYSIS OF APPLICABILITY OF X-12-ARIMA METHOD FOR FORECASTING AND DECOMPOSITION OF PASSENGER DEMAND TIME SERIES (Perner's Contacts, 2012)
Identification and description of trend, seasonality, ongoing changes in nature of main components of economic time series as well as its forecasting requires application of proper decomposition approach to its modelling and forecasting. The main purpose of the paper is to analyse applicability of the X-12-ARIMA decomposition procedure, which should eliminate limitations of X-11-ARIMA/88 method, in order to decompose of passenger demand for suburb bus transport time series. Applicability of X-12-ARIMA procedure was tested by several statistical tests, summary measures (M1-M7, Q1 and Q2) and goodness-of-fit measures. Outputs of the analyses proved applicability of X-12-ARIMA procedure in the process of passenger demand time series analysis.
Keywords: X-12-ARIMA, Passenger demand for suburb bus transport, Short-term passenger demand forecasting, Passenger demand time series seasonal adjustment